Weight Optimization in Crane Hook - Solanki, Mahesh; Bhatt, Antriksh; Rathour, Anilkumar; Thakkar, Smit (IJRDO - Journal of Mechanical And Civil Engineering, 2015)
Crane hook are highly liable component and are always subjected to failure due to accumulation of large amount of stress which can eventually lead to its failure .In this present work, to study the different design parameter & stress pattern of crane hook in its loaded condition for different cross section, the design and drafting of crane hook will be prepared using software. By finite element analysis, the stress which is to be formed in various cross section are compared with design calculation .The stress concentration factors are used in strength and durability evaluation of structure and machine element. So, here changing the cross sectional area, and removing material from low stress concentration area in lifting hook and then comparing design stress, the hook is to be optimized.